PERENCANAAN STRATEGIS MANAJEMEN KEUANGAN UNTUK SUKSES PENDIDIKAN DI SDN KAMPUNG BARU - Rahmulyana, Anjar; Yusuf, Furtasan Ali; Hayadi, B. Herawan; Yustiva, Fitriyatul; Junaesih, R.; Raman, Raman (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to explore the role of strategic planning in financial management to support educational success at the Kampung Baru State Elementary School (SDN). Through a qualitative approach involving in-depth interviews, participant observation, document analysis, and focus group discussions (FGD), this research highlights challenges, best practices, and recommendations for improving financial management in these schools. The research results reveal that SDN Kampung Baru faces significant challenges in managing limited financial resources, including a lack of funding and increasing operational costs. However, best practices such as careful budget management and active participation from stakeholders have been identified as important factors in improving the effectiveness of school financial management. Strategic recommendations resulting from this research include the development of a long-term financial strategic plan that involves participation from all relevant parties, increasing transparency and accountability in school financial management. This research also contributes to a better understanding of the importance of strategic planning in the context of school financial management and provides a foundation for further research in this area